Structure № 18 of ‘Near Suburbs’ of Dykyi Sad Fortified Settlement - Kyrylo Horbenko; Leonid Smyrnov; Yurii Zhyrok (Емінак, 2023)
The purpose of the research paper is to characterize and determine the arrangement and constructional features of structure № 18 located within the territory of the ‘Near Suburbs’ of Dykyi Sad fortified settlement dated to the Final Bronze Age (12/13-12/11 centuries BCE).